Investment strategy development of the Siberian Federal District within the framework of implementation of the regional investment standards - E. A. Fedulova (Контуры глобальных трансформаций: политика, экономика, право, 2014)
The author considers the mechanism of implementation of the regional investment standard’s first section. The article analyzes the methodological approaches to the regional investment strategy development in the regions of SFD, identifies common problems and provides recommendations to overcome them.